ANALISIS PENGARUH KEPEMIMPINAN VISIONER, KOMPETENSI DAN STRES KERJA TERHADAP PRODUKTIVITIAS KERJA KARYAWAN PADA PT. ALFO CITRA ABADI MEDAN - Simbolon, Sahat (Jurnal Manajemen dan Bisnis, 2024)
This research aims to explore the influence of visionary leadership, competence, and work stress on employee productivity at PT. Alfo Citra Abadi Medan. The study involves 107 employees selected through simple random sampling from a total population of 147 in the production division. Data was collected using a questionnaire and analyzed through various tests, including validity, reliability, descriptive analysis, multicollinearity, heteroscedasticity, Glejser, normality, multiple linear analysis, linear correlation coefficient, partial hypothesis (t-test), simultaneous hypothesis (F-test), and determination coefficient calculation. Descriptive analysis results indicate that visionary leadership, competence, and work stress at PT. Alfo Citra Abadi Medan are considered satisfactory. Partial analysis reveals positive and significant influences of visionary leadership and competence on employee productivity, while work stress negatively and significantly affects productivity. Simultaneously, visionary leadership, competence, and work stress collectively have a positive and significant impact on employee productivity, explaining 41.5% of the variation, with the remaining 58.5% influenced by unexamined variables like motivation and work environment.